PD-1 and CTLA-4 serve as major gatekeepers for effector and cytotoxic T-cell potentiation by limiting a CXCL9/10-CXCR3-IFNγ positive feedback loop - Abdala-Saleh, Noor; Lugassy, Jennie; Shivakumar-Kalvhati, Akshatha; Turky, Abeer; Abu Ras, Sari; Razon, Hila; Berger, Nir; Bar-On, Dana; Bar-On, Yotam; Taura, Tetsuya; Wilson, David; Karin, Nathan (Frontiers in Immunology, 2024)
CXCR3 is a chemokine receptor with three ligands: CXCL9, CXCL10 and CXCL11. We report that in addition to attracting CXCR3+ T cells to tumor sites a key role of CXCL9 and CXCL10 is in inducing a self-feeding feedback loop that accelerates effector/cytotoxic activities of both CD4+ and CD8+ T cells while downregulating immunoregulatory protein TIM3. CXCR3KO mice displayed a markedly reduced response to anti-PD-1 and anti-CTLA-4 therapy. Results from a panel of in vivo and ex vivo 3D tumor models imply that, beyond driving CD8+ T cells into T-cell exhaustion, a major role of PD-1 and CTLA-4 is in limiting the CXCR3-based self-feeding mechanism of T cell potentiation. This may explain why patients that are CXCL9/CXCL10high tend to respond well to anti-PD-1 therapy, as opposed to patients that are CXCL9/CXCL10low. It also suggests a therapeutic role for CXCL9-Fc or CXCL10-Fc therapy; herein we demonstrate significant anti-tumor activity in multiple murine tumor models with such agents.